Protein level varicus tissues of the prawn, Penaeus merguiensis De Man (Crustacea decapoda,penaeidae) at different stages of ovarian maturation - Mohamed Kamil Abdul Rashid (Fakulti Pengajian Maritim dan Sains Marin, 2011)
I am greatly indebted to my supervisor, Dr. Chan H. H. for her invaluable advice, guidance and suggestion throughout course of this study. Her deep concern for my work and generous sacrifice of her precious time correcting this manuscript is also deeply appreciated.